Inside Daisy Clover [videorecording (DVD)] - Mulligan, Robert, 1925-2008; Wood, Natalie; Plummer, Christopher; Redford, Robert; McDowall, Roddy; Gordon, Ruth, 1896-1985; Lambert, Gavin (Distributed by Warner Home Video, 2009)
Daisy Clover is a 15 year old Tomboy who dreams of being a Hollywood star. After auditioning for producer Raymond Swan of Swan Studios she becomes the toast of Hollywood. Daisy must then come to terms with her new found fame and the 1930's Hollywood star treatment. She is considered a has-been by the time she turned seventeen. Daisy's meteoric rise to stardom and even faster fade-out is chronicled in an incisive behind-the-scene tour of vintage Hollywood.